Periodontal Diseases - A Clinician's Guide 2012
DOI: 10.5772/28578
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Diseases in Greek Senior Citizens-Risk Indicators

Abstract: Aim: This study provides data on the periodontal status of Greek adults aged 35–44‐years‐old in relation to socio‐demographic and behavioural parameters and compares these data with those of 1985. Material and methods: A stratified cluster sample was selected according to WHO guidelines for national pathfinder surveys. Periodontal and oral hygiene status were assessed using the CPI index and the OHI‐S index respectively. Socio‐demographic and behavioural data were collected through face‐to‐face interviews. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 39 publications
1
16
1
2
Order By: Relevance
“…Therefore, low incomes and low levels of education seem to be variables with good predictability for periodontal diseases 7 . The prevalence of gingival inflammation in females found in the present study contradicts results from Greece, where women have been shown to have better oral hygiene and gingival status than men 22 . Perhaps this difference is more about culture than gender.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, low incomes and low levels of education seem to be variables with good predictability for periodontal diseases 7 . The prevalence of gingival inflammation in females found in the present study contradicts results from Greece, where women have been shown to have better oral hygiene and gingival status than men 22 . Perhaps this difference is more about culture than gender.…”
Section: Discussioncontrasting
confidence: 99%
“…Although epidemiologic studies indicate consistently that gingival inflammation is a highly prevalent condition, there is heterogeneity in the reported prevalence of gingivitis (Table 1). [19][20][21][22][23][24][25][26][27][28][29][30] Even though part of this heterogeneity can be interpreted in the light of real, genuine differences in disease occurrence among studied populations, it is evident that differences among cohorts may well be related to variations in the diagnostic criteria used to define a GC.…”
Section: From Gingival Inflammation To Gingivitis Case Definitionmentioning
confidence: 99%
“…Epidemiological studies have based the GC definition on epidemiological indices (Table 1) [19][20][21][22][23][24][25][26][27][28][29][30] such as: the Community Periodontal Index of Treatment Need (CPITN/CPI); average severity of gingival inflammation (as assessed using gingival indices or bleeding scores); average extent of gingival inflammation (assessed as the prevalence of sites with a certain gingival index or bleeding score); combinations of severity and extent measures. The majority of epidemiologic studies investigating the prevalence of periodontal diseases, including gingivitis, are based on the use of CPITN.…”
Section: From Gingival Inflammation To Gingivitis Case Definitionmentioning
confidence: 99%
“…These criteria were fulfilled by only four studies [10, 11••, 14, 25], raising the validity of these studies as opposed to the other studies. Only partial information on inter-or intra-reliability measures was reported in five studies [9,12,13,15,16], while for the UK Adult Dental Health Survey, calibration data for PPD were not available at all [23,57].…”
Section: Issues Of Examiner Reliabilitymentioning
confidence: 99%
“…Only few studies have monitored the trend of periodontal prevalence and severity over the last decades, with four additional epidemiologic studies being published [8][9][10]11••] after the last review [2•]. For this review, five national (England, Germany, New Zealand, USA, and Greece) and five regional [Pomerania (North-East Germany), Thun (Switzerland),´s-Hertogenbosch (The Netherlands), Jönköping (Sweden) and Oslo (Norway)] studies were considered.…”
Section: Introductionmentioning
confidence: 99%